Technology Readiness of Retail MSMEs for Digital Sales: Evidence from Kramat, Tegal - Sarif Surorejo; Nugroho Adhi Santoso; Divia Faiqotul Cahyati (Brilliance: Research of Artificial Intelligence, 2025)
Digital transformation has become a key driver for enhancing the competitiveness and sustainability of Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the digitalization readiness of retail MSMEs in Kramat District, Tegal Regency, by applying the Technology Readiness Index (TRI) model consisting of four dimensions: optimism, innovativeness, discomfort, and insecurity. A quantitative survey method was employed involving 70 MSME respondents, and data were analyzed using descriptive statistics. The findings reveal that optimism (3.45), discomfort (3.37), and insecurity (3.32) fall into the high category, while innovativeness (2.75) is in the medium category. Item-level analysis shows that Q4 (optimism) recorded the highest score (3.59), reflecting a strong belief in the benefits of technology, whereas Q7 (innovativeness) obtained the lowest (2.26), indicating low initiative in adopting new digital tools. These results suggest that retail MSMEs in Kramat District have a positive perception of technology but remain cautious in terms of proactive innovation. The study concludes that enhancing innovativeness through digital skills training, mentoring, and policy support is essential for accelerating MSME digital transformation. This research contributes to the literature by providing empirical evidence from a semi-urban context in Indonesia and offers practical recommendations for policymakers and stakeholders in strengthening MSME competitiveness in the digital era.